DESAIN SISTEM MONITORING FLOWMETER KOMUNIKASI RS 232 MENGGUNAKAN SOFTWARE NODE-RED PADA FUEL CELL ELECTRIC VEHICLE: Design of RS 232 Communication Flowmeter Monitoring System using Node-Red Software for Fuel Cell Electric Vehicle - Yulianti, Dinda; Ifa Fauziah; Hamid Abdillah; Kurniawan; Irma Yulianti (Universitas Negeri Jakarta, 2023)
One of the applications of fuel cells is Fuel Cell Electric Vehicles (FCEV). FCEV is more efficient and produces no carbon emissions than conventional internal combustion engine vehicles. FCEV emitting only water vapor and warm air. This research hoped will provide new knowledge regarding the monitoring system for hydrogen output in FCEVs using the Node-RED software application, as well as regarding flowmeters with RS 232 output. The design of this serial flowmeter monitoring system was carried out in the fuel cell laboratory, the Energy Conversion and Conservation Research Center (PRKKE). This research was carried out by direct observation of the laboratory where fuel cell electric cars were studied, and collected data directly in the laboratory. The Node-RED flow design begins by providing a timestamp every 10 seconds when FCEV is operated, debugging to determine how the results of trials and failures occur. When FCEV is operated, a tenth of a second of data from the flowmeter enters the Moxa Nport device server. This monitoring design combines the Moxa NPort 5230 device server, battery supply, flowmeter with RS232 communication, and several electronic circuits. The flowmeter testing experiment for hydrogen output data on Fuel Cell Electric Vehicles obtained 1.38 with a speed of 1.46 l/min.